Effect of cover crops on microbial community structure and related enzyme activities and macronutrient availability - Chavarría, Diego Nicolás (2016)
Continuous monoculture in major agricultural regions has been characterized by the loss of fertility, increased soil erosion and surface runoff. Thus, the inclusion of cover crops (CC) is a promising option aimed at better preserving the sustainable production of agricultural systems. The objective of this studywas to assess the short-term effect of CC on soil microbial community structure and related enzyme activities and macronutrient availability. Species tested as CC were: oat (Avena sativa L.), vetch (Vicia sativa L.) and radish (Raphanus sativus L.), which were sown in two species mixtures, oat/radish (CC1) and oat/radish/vetch (CC2), with soybean monoculture and soybean/corn being the cash crops. The field trial was performed under no-tillage, and soil sampling was carried out in 2013 and 2014. The analysis of soil phospholipid fatty acid (PLFA) showed an increase of total bacterial PLFA and Gram-positive PLFA under CC treatments, being on average 6.8% significantly higher in CC2 and CC1 than in the control treatment. In addition, soil enzyme activities (esterase activity, dehydrogenase activity and acid phosphatase activity) were on average 20% higher in plots under CC in comparison to control treatments. The total N was significantly higher after CC2 treatment (3.13 mg g1) than in either the CC1 (2.00 mg g1) or control (2.19 mg g1). This research revealed that the inclusion of CC mixtures in crop rotation produced an increase in bacterial PLFA, in particular Gram-positive bacteria, in the short term. These changes were related to soil enzyme activities and to the availability of the main macronutrients N and P, with a CC mixture including oat/radish/vetch being highly recommended not only to improve soil biological processes but also to provide additional N to the cash crop.